2015
DOI: 10.1155/2015/197652
|View full text |Cite
|
Sign up to set email alerts
|

Comorbid Psychopathology and Alcohol Use Patterns among Methadone Maintenance Treatment Patients

Abstract: 130 patients from a methadone maintenance treatment program agreed to complete Symptoms Checklist 90-Revised (SCL-90R) and Alcohol Use Disorders Identification Test (AUDIT) self-report scales. Scores higher than the proposed cut-score on SCL-90R scale were observed on depression, obsessions-compulsions, paranoid ideation, anxiety, anger-hostility, somatization, interpersonal sensitivity, and psychoticism subscales. In sum, 42.9% of our sample exhibited depressive symptomatology, 34.9% obsessive-compulsive symp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 76 publications
(64 reference statements)
0
6
0
Order By: Relevance
“…Numerous studies have assessed alcohol use in heroin users receiving OAMT. 3,6,15,16,[25][26][27][28][29] However, very few studies from LAMIC report on alcohol and other drug use in heroin users who have received detoxification and psychosocial rehabilitation. Our study shows that initial decreases in heroin use were followed by a significant increase 6 months later.…”
Section: Discussionmentioning
confidence: 99%
“…Numerous studies have assessed alcohol use in heroin users receiving OAMT. 3,6,15,16,[25][26][27][28][29] However, very few studies from LAMIC report on alcohol and other drug use in heroin users who have received detoxification and psychosocial rehabilitation. Our study shows that initial decreases in heroin use were followed by a significant increase 6 months later.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, as hepatitis infection is a common comorbidity among opioid dependent individuals with prevalence estimates ranging from 64 to 100% in some cohorts [3944], chronic alcohol misuse can result in hepatotoxicity and increase an individual’s risk for progression to cirrhosis [11, 13, 15]. Additionally, alcohol misuse can exacerbate psychiatric comorbidities such as anxiety, depression and suicidality, all of which are known to be more common among OAT recipients [8, 10, 12, 45, 46]. Lastly, a study by Sebanjo et al demonstrated alcohol misuse to be associated with a significant reduction in quality of life and social functioning among methadone maintained individuals [14].…”
Section: Discussionmentioning
confidence: 99%
“…For instance, in the case of compulsive buying, Maraz et al [ 60 ] found an increased level of obsessive-compulsive symptoms among addicted shoppers compared to nonaddicted shoppers. Moussas et al [ 61 ] investigated patients of a methadone maintenance treatment program, and depression and obsessive-compulsive symptoms were found to have the highest mean scores among all the symptoms. Similarly, in the case of methamphetamine users, obsessive-compulsive symptoms and depression were reported to have the highest levels among the psychopathological symptoms, especially for injectors (compared to methamphetamine users who used other routes of administration) [ 62 ].…”
Section: Discussionmentioning
confidence: 99%